Determination of Optimum Dimension for the High Radioactive Waste Storage Container - Kim, Geun-Ho; Lee, Jong-Hwan; Jeong, Kwan-Seong; Hyun, Dongjun; Choi, Byung-Seon; Moon, Jeikwon (Asian Journal of Chemistry, 2014)
To design the reasonable decommissioning scenario, an evaluation to determine the optimum thickness of radioactive waste storage containers (20 and 40 ton) was performed in terms of the radiological and economic aspects. The optimum thickness was regarded as the minimum thickness that is not allowed over the criterion surface dose rate (2 mSv/h). The surface dose rate was calculated using the MCNP code based on the concentration of Co-60. The optimum thickness of a 20 ton storage container was estimated to be from 34.3 to 19.2 cm. The optimum thickness of a 40 ton storage container was also evaluated the same as that of the 20 ton storage container. This result was considered due to the self-absorption of the radiation source in which the thickness was 30 cm or more. The internal volume of the 40 ton storage container was about 4 times larger than that of the 20 ton storage container.